Development of Adobe Flash CS6 Multimedia-Based Learning Media on Science Subjects Animal Breeding Materials - Zulfadewina Zulfadewina; Adi Sucipto; Khairil Iba; Zulherman Zulherman (Jurnal Basicedu, 2020)
Learning during pandemic is a challenge in education; however, it is also an opportunity to create an innovation in education. This study aims to find result for developing learning media in animal breeding lesson using Adobe Flash Professional CS6, to find the feasibility of learning media on animal breeding lesson using Adobe Flash Professional CS6, to find student’s respond in class V on animal breeding lesson. Research method uses Research and Development (R&D) model by using development procedure, such as: analysis, which is conducting requirements identification. Model used by the researchers in this study is Borg and gall, which has 10 steps, they are: Research introduction/pre-survey, Planning, Developing model/initial product, Test by Expert, and initial Field test, Revising initial/limited field test result, Primary field test execution, Revising primary field test, Feasibility test/operational field test, Final revision result of feasibility test, Dissemination and Implementation of Final product. Product test is carried by media and material experts; teacher and students are also as respondents for media developed. This media is tested to 10 students as small group and 95 students from 3 different schools. Research result shows that material experts give 89% score, media expert gives 78% score, teachers give 90% score, and students give 93% score. So that, this research result means giving an innovation in education to support student learning interest.